Spatial analysis of cases of decision-making to sign residential investment projects within the administrative boundaries of the Municipality of Baghdad and their effects-Al-Ayadi residential complex as a model Abstract: (Journal of the College of Basic Education, 2022)
This research will deal in a simple way about the concept of place, spatial analysis and decision-making cases in order to truly arrive at the extent to which the decision taken in its various cases is appropriate (complete certainty, uncertainty, complete uncertainty), in light of the fulfillment of the conditions that must be met: (ease of access to services and transportation Adequacy of services, commitment to land uses according to the basic design) in the matter of deciding the spatial signature of residential investment projects within the administrative boundaries of the Municipality of Baghdad and its various axes of influence, which are: the axis of land uses, the demographic axis, the political and administrative axis, the planning aspect, the axis of community services and structures Underpinning, and reaching through it indicators that summarized the state of decision-making as a reality of the situation and approved it in the questionnaire of the concerned experts and specialists in the Baghdad Municipality to reach whether there are tangible effects of these axes and the case in which the decision was taken under the hypothesis of the research that there is a relationship linking the place to the decision-making, Bearing in mind that the research topic is derived from the researcher's unpublished master's thesis